The Influence of Problem-Solving Learning Model Assisted by Adventure Board Media on Students' Problem-Solving Ability - Putri Ayu Tyara; Lisa Virdinarti Putra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Problem-solving is one of the abilities that must be mastered by elementary school students, especially regarding learning to count. So the authors applied the problem-solving learning model using adventure board media to determine the effectiveness in dealing with this problem-solving ability. This research uses quantitative methods. This type of research is an experiment with a none-none equivalent control group design. The population in this study were students in class VA and VB Ungaran Elementary School 01. Data analysis techniques used the normality test, homogeneity test, and simple linear regression test. The results showed that there was an effect of the problem-solving learning model on students' problem-solving abilities using adventure board media on increasing students' problem-solving abilities as evidenced by t count = 4,864 > t table = 2,064 and a significance value of 0.000 <0.05 and influencing the problem-solving ability variable by 47.5%. So it can be concluded that the problem-solving learning model using adventure board media can affect students' problem-solving abilities